2015
DOI: 10.1074/jbc.m115.652669
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Formylglycine-generating Enzyme with Copper(II) for Aldehyde Tag Conversion

Abstract: Background: Aerobic formylglycine-generating enzyme (FGE) converts cysteine to formylglycine in vivo.Results: Purified FGE requires preactivation with copper to convert cysteine to formylglycine in vitro.Conclusion: FGE is a metalloenzyme. It is also a useful biocatalyst for the production of proteins that contain aldehyde tags.Significance: Understanding FGE biochemistry informs research on sulfatases and enables expanded biotechnology applications of the aldehyde tag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 52 publications
2
53
1
4
Order By: Relevance
“…While this manuscript was under review,a ni ndependent study,d escribing as imilar activating effect of copper on FGE from humansa nd from Streptomyces coelicolor,w as published in the Journalo fB iological Chemistry.T he two studies demonstrate the generality of copper-dependent activation of in vitro FGE activity. [16]…”
Section: Af Inal Notementioning
confidence: 99%
“…While this manuscript was under review,a ni ndependent study,d escribing as imilar activating effect of copper on FGE from humansa nd from Streptomyces coelicolor,w as published in the Journalo fB iological Chemistry.T he two studies demonstrate the generality of copper-dependent activation of in vitro FGE activity. [16]…”
Section: Af Inal Notementioning
confidence: 99%
“…[17] This recognition sequence can be introduced into recombinant proteins and converted by FGE in vivo or in vitro. [19][20][21][22] In addition, the iron-sulfur protein AtsB of the radical S-adenosyl methionine (radical-SAM) protein superfamily is another FGly-generating system that is exclusively found in prokaryotes. [19][20][21][22] In addition, the iron-sulfur protein AtsB of the radical S-adenosyl methionine (radical-SAM) protein superfamily is another FGly-generating system that is exclusively found in prokaryotes.…”
mentioning
confidence: 99%
“…The catalytic mechanism of FGE is not yet fully understood. Recent work, however, showed that FGE is a copper‐dependent oxidase that might take an approach to O 2 activation and C−H cleavage similar to that of the copper‐dependent lytic polysaccharide monooxygenases (LPMOs), the peptidylglycine α‐hydroxylating monooxygenase, or dopamine/tyramine‐β‐monooxygenases . In the course of isolating the catalytic principle of FGE from T. curvata we constructed a variant in which all cysteine residues outside the active site were mutated .…”
Section: Resultsmentioning
confidence: 99%
“…Because the phenol function of Tyr273 does not directly contribute to catalysis we considered alternative roles for this residue. Tyr273 could be a copper ligand and might contribute to the high Cu I affinity . Indeed, tyrosine residues do function as copper ligands in other mononuclear copper enzymes such as galactose oxidase, copper amine oxidases, and type‐AA9 LPMOs .…”
Section: Resultsmentioning
confidence: 99%